Effect of Extract Euphorbia hirta Linn. Against Leaf and Fruit Pests on Plants Cucumber (Cucumis sativus Linn.) - Rahmah, Aulia; Pramudi, Muhammad Indar; Aidawati, Noor; Aphrodyanti, Lyswiana (International Journal of Environment, Agriculture and Biotechnology, 2023)
Euphorbia hirta which is commonly known as "patikan kebo" is small herb which gives milky latex. This study aims to determine the effect of E. hirta extract in reducing the intensity of leaf and fruit pest attacks on cucumber plants Cucumis sativus Linn. The results of this study showed that all treatments with this extract were able to suppress the intensity of pest attacks on cucumber plants and had a significant effect on reducing the intensity of pest attacks on cucumber plants. The best concentration that can reduce the intensity of these pest attacks is the treatment of 10% can reduce the intensity of leaf pest attacks on cucumber plants up to 4.64%. The intensity of pest attacks on cucumbers only occurred in the control and 2% extract treatment with percentages of damage intensity to cucumbers of 9.38% and 3.13%.